On the importance of spiral‐flow inflow boundary conditions when using idealized artery geometries in the analysis of liver radioembolization: A parametric study. (17th April 2020) - Ortega, Julio; Antón, Raul; Ramos, Juan C.; Rivas, Alejandro; Larraona, Gorka S.; Sangro, Bruno; Bilbao, Jose I.; Aramburu, Jorge
Abstract: In the last decades, the numerical studies on hemodynamics have become a valuable explorative scientific tool. The very first studies were done over idealized geometries, but as numerical methods and the power of computers have become more affordable, the studies tend to be patient specific. We apply the study to the numerical analysis of tumor‐targeting during liver radioembolization (RE). RE is a treatment for liver cancer, and is performed by injecting radiolabeled microspheres via a catheter placed in the hepatic artery. The objective of the procedure is to maximize the release of radiolabeled microspheres into the tumor and avoid a healthy tissue damage. Idealized virtual arteries can serve as a generalist approach that permits to separately analyze the effect of a variable in the microsphere distribution with respect to others. However, it is important to use proper physiological boundary conditions (BCs). It is not obvious, the need to account for the effect of tortuosity when using an idealized virtual artery. We study the use of idealized geometry of a hepatic artery as a valid research tool, exploring the importance of using realistic spiral‐flow inflow BC. By using a literature‐based cancer scenario, we vary two parameters to analyze the microsphere distribution through the outlets of the geometry. The parameters varied are the type of microspheres injected and the microsphere injection velocity. The results with realistic inlet velocity profile showed that the particle distribution in the liver segments is not affected by the analyzed injection velocity values neither by the particle density. Novelty Statement: In this article, we assessed the use of idealized geometries as a valid research tool and applied the use of an idealized geometry to the case of an idealized hepatic artery to study the particle‐hemodynamics during radioembolization (RE). We studied three different inflow boundary conditions (BCs) to assess the usefulness of the geometry, two types of particle injection velocities and two types of commercially available microspheres for RE treatment. In recent years, the advent in computational resources allowed for more detailed patient‐specific geometry generation and discretization and hemodynamics simulations. However, general studies based on idealized geometries can be performed in order to provide medical doctors with some basic and general guidelines when using a given catheter for a given cancer scenario. Moreover, using an idealized geometry can be a reasonable approach which allows us to isolate a given parameter and control other parameters, so that parameters can be independently assessed. Even though an idealized geometry does not match any patient's geometry, the use of an idealized geometry can be valid when drawing general conclusions that may be useful in patient‐specific cases. However, we believe that even if an idealized hepatic artery geometry is used for the study, it is necessary to account for the upstream and downstream tortuosity of vessels through the BCs. In this work, we highlighted the need of modeling the tortuosity of upstream and downstream vasculatures through the BCs. Abstract : Using an idealized hepatic geometry, is necessary to take into account a boundary condition (BC) that represents the tortuosity that is representative of those arteries. This can be done by using a physiologically realistic spiral flow as an inflow BC. Once realistic BCs are used, some parameters can be controlled and analyzed (ie, microsphere type and particle injection velocity). This type of arterial geometries would become an interesting and useful tool to perform quick and reliable numerical particle‐fluid dynamics simulations.